Comparison of Needle Insertion and Guidewire Placement Techniques During Internal Jugular Vein Catheterization. Issue 10 (October 2015) - Lee, Yong Hun; Kim, Tae Kyong; Jung, Yoo Sun; Cho, Youn Joung; Yoon, Susie; Seo, Jeong-Hwa; Jeon, Yunseok; Bahk, Jae Hyon; Hong, Deok Man
<x xml:space="preserve">Abstract</x> Objectives: For needle insertion and guidewire placement during central venous catheterization, a thin-wall introducer needle technique and a cannula-over-needle technique have been used. This study compared these two techniques regarding the success rates and complications during internal jugular vein catheterization. Design: Prospective, randomized, controlled study. Setting: A university-affiliated hospital. Patients: Two hundred sixty-six patients scheduled for thoracic surgery, gynecologic surgery, or major abdominal surgery, who required central venous catheterization. Interventions: Patients were randomly assigned to either the thin-wall introducer needle group (n = 134) or the cannula-over-needle group (n = 132). Central venous catheterization was performed on the right internal jugular vein under assistance with real-time ultrasonography. Needle insertion and guidewire placement were performed using a thin-wall introducer needle technique in the thin-wall introducer needle group and a cannula-over-needle technique in the cannula-over-needle group. Measurements and Main Results: The guidewire placement on the first skin puncture was regarded as a successful guidewire insertion on the first attempt. The number of puncture attempts for internal jugular vein catheterization was recorded. Internal jugular vein was assessed by ultrasonography to identify complications. The rate of successful guidewire insertion on the first attempt was higher in the thin-wall introducer needle group compared with the cannula-over-needle group (87.3% vs 77.3%; p = 0.037). There were fewer puncture attempts in the thin-wall introducer needle group than in the cannula-over-needle group (1.1 ± 0.4 vs 1.3 ± 0.6; p = 0.026). There was no significant difference in complications of internal jugular vein catheterization between the two groups. Conclusions: The thin-wall introducer needle technique showed a superior success rate for first attempt of needle and guidewire insertion and required fewer puncture attempts during internal jugular vein catheterization.